Transactive energy system: Concept, configuration, and mechanism - Zhou, Hai; Li, Biao; Zong, Xingchen; Chen, Dawei (Frontiers in Energy Research, 2023)
Transactive energy system (TES), which combines both economical and control mechanisms, becomes a high-potential solution to integrate distributed energy resources (DERs) in modern power systems. In this paper, the basic concept of TE, including definition, process, time scale, and its benefits is briefly introduced first. Then the configuration of the transactive energy system is described in detail from the perspectives of the physical system, information system, transaction system and regulatory system. The transaction mechanism allows participants (customer, generator, transmission operator, marketer, etc.) to conduct various transactions with any other party to the extent regulatory policy permits. Transactive control is regarded as one of the most advanced approaches which realize the full response potential of flexible devices and respect the privacy, preference and free will of end users. Some challenges of the development of transactive energy systems are comprehensively discussed from the limitations of current equipment level and methodological concepts. In summary, the transactive energy system provides a more efficient, fair and transparent environment for participants to promote DERs utilization, improve market efficiency and increase economic benefits.